Improved longevity and in vivo performance of neurotransmitter detection using 30 µm cone-shaped carbon fiber microelectrode - Kwon, Haeun; Cho, Hyun-U; Sim, Jeongeun; Boo, Kyung-Jun; Kang, Yumin; Hwang, Sangmun; Kwak, Youngjong; Jang, Jaehyun; Kim, Kyung Min; Jeon, Se Jin; Shin, Chan Young; Bennet, Kevin E.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Fast Scan Cyclic Voltammetry (FSCV) is a widely used electrochemical technique to detect rapid extracellular dopamine transients in vivo. It employs carbon fiber microelectrodes (CFMEs), but conventional 7 µm diameter CFMEs often suffer from limited mechanical durability and reduced lifespan, hindering their use in chronic monitoring. To improve mechanical robustness and long-term functionality, we fabricated 30 µm diameter CFMEs and modified their geometry via electrochemical etching to form cone-shaped tips. We compared the in vitro and in vivo performance of 7 µm, 30 µm bare, and 30 µm cone-shaped CFMEs using FSCV. Electrode longevity was assessed, and biocompatibility was evaluated via immunofluorescence analysis of brain tissue. In vitro, the 30 µm bare CFMEs showed 2.7-fold higher sensitivity (33.3 ± 5.9 pA/µm2, n = 5) compared to 7 µm CFMEs (12.2 ± 4.9 pA/µm2, n = 5). However, in vivo dopamine detection was significantly reduced in 30 µm bare CFMEs (12.9 ± 8.1 nA, n = 5) relative to 7 µm CFMEs (24.6 ± 8.5 nA, n = 5), likely due to tissue damage. Cone-shaped modification of 30 µm CFMEs resulted in a 3.7-fold improvement in vivo dopamine signals (47.5 ± 19.8 nA, n = 5) and significantly lower glial activation based on Iba1 and GFAP markers. Furthermore, erosion tests revealed a 4.7-fold increase in lifespan compared to 7 µm CFMEs. These results suggest that while increasing CFME diameter improves sensitivity, it also increases tissue damage in vivo. The cone-shaped geometry effectively mitigates insertion-induced damage, enhancing in vivo performance and biocompatibility. This design offers a promising approach for long-term neurotransmitter monitoring and potential integration into closed-loop neuromodulation systems.